2014
DOI: 10.1007/s00192-014-2507-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in urethral sphincter size following rehabilitation in older women with stress urinary incontinence

Abstract: Introduction and hypothesis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…At week 12, the change was −4.1 (−5.4 to −2.8) and −6.6 (−7.3 to −5.8), respectively. A previous study investigated the effects of a pelvic floor muscle rehabilitation programme among elderly women with SUI (age >60 years); after 12-week intervention, the 3-day leakage episodes decreased from 4.6±4.2 to 1.1±1.6 (p=0.003), which were similar to our results 28. Changes from the baseline of the AUL were measured by 1-hour pad test, which is used to quantify urine leakage due to SUI.…”
Section: Discussionsupporting
confidence: 90%
“…At week 12, the change was −4.1 (−5.4 to −2.8) and −6.6 (−7.3 to −5.8), respectively. A previous study investigated the effects of a pelvic floor muscle rehabilitation programme among elderly women with SUI (age >60 years); after 12-week intervention, the 3-day leakage episodes decreased from 4.6±4.2 to 1.1±1.6 (p=0.003), which were similar to our results 28. Changes from the baseline of the AUL were measured by 1-hour pad test, which is used to quantify urine leakage due to SUI.…”
Section: Discussionsupporting
confidence: 90%
“…Adequate pelvic floor muscle (PFM) function may prevent or improve pelvic floor disorders . Clinical PFM evaluation incorporates imprecise and subjective integer scales, and overlooks dynamic properties which may be relevant to understanding the pathomechanics of pelvic floor disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Wiseman et al showed that urethra‐sphincter complex volumes (USCv) measured with ultrasonography can be used as a proxy for the MUCP, with enlarged USCv correlating with raised MUCP . USCv can also be measured on MRI with less operator dependence …”
Section: Introductionmentioning
confidence: 99%